VD_FINDINFO HC / 2010 / 336 vom 21. Juni 2010 - VD Tribunal cantonal (2010)
CAPACITÉ D'ESTER EN JUSTICE, CAPACITÉ PARTIELLE D'EXERCER LES DROITS CIVILS | 444 al. 1 ch. 2 CPC, 29 LPEBL, 4 al. 2 LPEBL, 9 LPEBL